An efficient hybrid technique for message encryption using caesar cipher and deoxyribonucleic acid steganography - Yalmaz Najm Aldeen Taher; Kameran Ali Ameen; Ahmed M. Fakhrudeen (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Due to security threats on data transmission, a combination of cryptography and steganography techniques are becoming increasingly popular and widely adopted. Correspondingly we have also witnessed most of the literature uses steganography systems development that depends on deoxyribonucleic acid (DNA). However, they are not sufficient to accommodate data security needs nowadays. Therefore, we propose a new cryptographic technique that combines Caesar cipher and DNA cryptography without affecting its functionality or type. In the beginning, a cryptography method encodes the original message and then conceals it into any cover medium by steganography methods. Comparison experiments have been conducted to verify the effectiveness of our proposal. The results demonstrate that our technique outperforms its counterpart in terms of time and complexity.